Aplikasi Geometri pada Permainan Dinamis Non-Kooperatif Skalar Waktu tak Berhingga - Nilwan Andiraja (UIN Sultan Syarif Kasim Riau, 2015)
In this research was discuss about to find equilibrium Nash in non-cooperative dynamic game two-player with scalar case for infinite time, by application the analytic geometry. Discuss was started from made of equation model for non-cooperative dynamic game two-player with scalar case for infinite time based on equation of non-cooperative dynamic game for infinite time. Then made of two the algebraic Riccati equation and control vector for each player. The control vector is used for made of stability condition of game. Then is used the curse of analytic geometry for analyse equilibrium Nash for dynamic game. Base on analyse, there are two algebraic Riccati equation which it is special case of the algebraic of second degree which it is hyperbolic equation. Then, based on of stability condition of game then equilibrium Nash can get from intersection point of two hyperbolic in adequate area for stability condition of game.Keywords: Dynamic, Game ,Geometry, Riccati, Scalar